CORRELATION OF ALBUMIN/ CREATININE URINE RATIO (ACR) CHANGES ON MORTALITY OF SEPTIC PATIENTS IN HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Mohd Faisyal Reza*, Tambar Kembaren, Restuti Hidayani Saragih & Nelly Elfrida Samosir (International Journal of Research Science and Management, 2019)
Introduction : Microalbuminuria has proven to be a predictor of organ function failure in septic patients. Microalbuminuria assessed by calculating ratio of urine albumin/ creatinine could be used as a simple, noninvasive to assess prognosis and predict mortality in early septic patients. Method : Thirty one septic patients weretaking urine samples for examination of albumin levels in the urine using urine albumin/ creatinine ratio (ACR). Patients also were observed for a maximum of 28 days to assess mortality. Result : Mortality of septic was found in 21 subjects (67.7%). Pneumonia was the most common source of infection (58.1%). Changes in ACR (p=0.02) and ACR II value (p=0.016) had a significant correlation with mortality in septic patients. In the contrary, no significant correlation was found between age, sex, vital signs, and source of infection with mortality of septic patients (p> 0.05). Hb values, platelets, ad random blood sugar, procalcitonin,urea and creatinine also did not have a significant correlation with mortality in septic patients (p> 0.05). Conclusion : This study suggested association between changes in ACR and ACR II with mortality of septic patients. The higher the value of ACR II would resulted in higher the patient mortality.